2007
DOI: 10.1196/annals.1404.001
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis Is a Novel Determinant of Aging in Caenorhabditis elegans

Abstract: Protein synthesis is a tightly regulated cellular process that affects growth, reproduction, and survival in response to both intrinsic and extrinsic cues, such as nutrient availability and energy levels. A pronounced, age-related decline of the total protein synthesis rate has been observed in many organisms, including humans. The molecular mechanisms underlying this decline and their role in the aging process remain unclear. A series of recent studies in the nematode, Caenorhabditis elegans, have revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 26 publications
(67 reference statements)
3
39
0
1
Order By: Relevance
“…The nucleolus is a key promoter of cellular anabolism (Dimario, 2004) and its activity is reduced in response to several genetic and pharmacological interventions that are known to extend lifespan (Grewal et al, 2007; Hoppe et al, 2009; Iadevaia et al, 2012; Zhang et al, 2000). In line with the notion that a moderate reduction in cellular anabolism and translation delays aging (Hansen et al, 2007; Kenyon, 2010; Pan et al, 2007; Steffen et al, 2008; Syntichaki et al, 2007), we have found that decreasing nucleolar function is a protective response induced to counteract aging and sufficient to extend lifespan.…”
Section: Discussionsupporting
confidence: 88%
“…The nucleolus is a key promoter of cellular anabolism (Dimario, 2004) and its activity is reduced in response to several genetic and pharmacological interventions that are known to extend lifespan (Grewal et al, 2007; Hoppe et al, 2009; Iadevaia et al, 2012; Zhang et al, 2000). In line with the notion that a moderate reduction in cellular anabolism and translation delays aging (Hansen et al, 2007; Kenyon, 2010; Pan et al, 2007; Steffen et al, 2008; Syntichaki et al, 2007), we have found that decreasing nucleolar function is a protective response induced to counteract aging and sufficient to extend lifespan.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, one could expect that, by increasing the protein turnover rate, cellular damage accumulation is prevented and the lifespan is extended. However, several studies are in conflict with the turnover hypothesis, as they observe overall decreased protein synthesis rates in C. elegans longevity mutants, or, vice versa, translation inhibition results in lifespan extension (Depuydt et al, 2013; Hansen et al, 2007; Pan et al, 2007; Stout et al, 2013; Syntichaki et al, 2007; Van Raamsdonk and Hekimi, 2009; Yang et al, 2007). Therefore, we hypothesized that, in daf-2 mutants, energy is saved by downregulation of turnover of the majority of proteins and reinvested in prioritized turnover of specific proteins that are crucial to somatic maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, it is expected that increased protein turnover rates would help to maintain a young undamaged proteome and extend the lifespan. However, in yeast and C. elegans , genetically induced attenuation of protein synthesis extends, rather than shortens, the lifespan (Hansen et al, 2007; Kaeberlein et al, 2005; Pan et al, 2007; Syntichaki et al, 2007). Moreover, classical 35 S pulse-chase labeling and quantitative proteomic studies suggest that low overall protein synthesis is a hallmark of long-lived C. elegans , either by dietary restriction or by mutation in the insulin signaling pathway (Depuydt et al, 2013, 2016; Stout et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because PRPS17 is a component of the plastid ribosome, the reduced expression of PRPS17 in the ore4 mutant is expected to result in reduced translation rate in the chloroplast. Similarly, several recent studies in C. elegans and Drosophila have revealed a link between protein synthesis and aging, and have shown that reduced mRNA translation extends lifespan (Arquier et al, 2005;Hansen et al, 2007;Syntichaki et al, 2007). Further characterization of PRPS17 might provide important insights into the relationship between translational regulation of plastid genes and leaf senescence.…”
Section: Translational Regulationmentioning
confidence: 90%